Biotin tethered homotryptamine derivatives: high affinity probes of the human serotonin transporter (hSERT) - Tomlinson, Ian D. (2011)
Quantum dot conjugates of compounds capable of inhibiting the serotonin transporter (SERT) could form the basis of fluorescent probes for live cell imaging of membrane bound SERT. Additionally, quantum dot-SERT antagonist conjugates may be amenable to fluorescence-based, high-throughput assays for this transporter. This paper describes the synthesis of SERT-selective ligands amenable to conjugation to quantum dots via a biotin-streptavidin binding interaction. SERT selectivity and affinity were incorporated into the ligand via a tetrahydropyridine or cyclohexylamine derivative and the affinity of these compounds for SERT was measured by their ability to produce SERT-dependent currents in Xenopus laveis oocytes.